Pengembangan Media Ajar Materi Sepak Bola Siswa Kelas VII SMP melalui Aplikasi Canva - Nanda Sulistyo Adji; Destriani Destriani (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to develop instructional media for football learning materials for seventh-grade junior high school students using the Canva application and to determine the feasibility and practicality of the developed media. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The study was conducted at SMP Negeri 4 Keluang, involving seventh-grade students as research subjects. Data collection techniques included material expert validation sheets, media expert validation sheets, teacher response questionnaires, and student response questionnaires. The results of material expert validation showed a percentage of 96%, categorized as very valid, while media expert validation reached 84%, also categorized as very valid. The practicality test results indicated that teacher responses achieved 100% with a very practical category, and student responses during the implementation stage reached 88.2% with a very practical category. The findings indicate that football instructional media based on the Canva application is feasible and practical for use in physical education learning at the junior high school level and can enhance students’ interest and understanding of football materials.